Eutrophication and phytoplankton in the Liffey Estuary and Dublin Bay - O'Higgins, Tim (Trinity College (Dublin, Ireland). Department of Zoology, 2006)
Temperature, salinity, nutrient and chlorophyll concentrations, and Secchi depth were measured monthly at 41 stations in the Liffey estuary and Dublin Bay from June 2000 to June 2004. Analysis of nutrient composition and suspended solid concentrations was made daily on sewage effluent from the Ringsend sewage treatment plant during the same period. During this time the plant was being upgraded from primary to secondary treatment (sequential batch reactors).
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin